2020
DOI: 10.1186/s12902-020-00593-6
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of long non-coding RNA expression profiles in high-glucose treated vascular endothelial cells

Abstract: Background: Diabetes mellitus is often associated with microvascular and macrovascular lesions, and hyperglycemia-induced vascular endothelial cell damage is a key factor. Methods: We investigated long non-coding RNAs (lncRNAs) and mRNAs that are affected by hyperglycemiainduced damage using human umbilical vein endothelial cells (HUVECs) as a model. HUVECs were cultured under high (25 mmol/L) or normal (5 mmol/L) glucose conditions for 6 d, and then lncRNAs and protein-coding transcripts were profiled by RNA-… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 46 publications
0
9
0
Order By: Relevance
“…2 Healthy endothelial cells are the basis of normal blood vessels, whereas endothelial cell dysfunction is a risk indicator of diabetic angiopathy. 3 Accumulating evidence indicated that diabetes-related microvascular complications result from genetic and environmental interactions. 4,5 Long non-coding RNAs (lncRNAs), which are >200 nucleotides in length, are emerging regulatory non-coding RNAs, participate in epigenetic and transcriptional/ post-transcriptional regulation of several cellular pathways in different diseases, including DM and its complications.…”
Section: Introductionmentioning
confidence: 99%
“…2 Healthy endothelial cells are the basis of normal blood vessels, whereas endothelial cell dysfunction is a risk indicator of diabetic angiopathy. 3 Accumulating evidence indicated that diabetes-related microvascular complications result from genetic and environmental interactions. 4,5 Long non-coding RNAs (lncRNAs), which are >200 nucleotides in length, are emerging regulatory non-coding RNAs, participate in epigenetic and transcriptional/ post-transcriptional regulation of several cellular pathways in different diseases, including DM and its complications.…”
Section: Introductionmentioning
confidence: 99%
“…Xu et al characterized the lncRNA landscape of expression, and found that 214 lncRNAs were upregulated and 197 were downregulated in highglucose cultured human umbilical vein endothelial cells (HUVECs). 62 Further research should focus on these dysregulated lncRNAs to provide novel insights into the regulatory molecules of diabetes-induced endothelial dysfunction. Hyperglycemic conditions also cause damage to endothelial progenitor cells (EPCs).…”
Section: Role In Diabetic Microvascular Injurymentioning
confidence: 99%
“…The majority of lncRNAs that have been identified and characterized have been in diseases. This include cancers (Jin et al, 2020;Teppan et al, 2020;Zhou et al, 2020;Katsushima et al, 2021), diabetes (Taheri et al, 2020;Xu E. et al, 2020;Ismail et al, 2021), cardiovascular diseases (Fang et al, 2020;Meng et al, 2020;Yeh et al, 2020) and ischemic stroke (Gan et al, 2021;Wolska et al, 2021). In this section, we will focus on angiogenic lncRNAs enriched in disease and their epigenetic functions.…”
Section: Angiogenic Lncrnas In Diseasementioning
confidence: 99%